Magnetic Pulse Compaction of Oxide Powders of the (ZrO[2] – Y[2]O[3]) – Al[2]O[3] System; Advanced Materials Research; Vol. 1040 : High Technology: Research and Applications 2014 (HTRA 2014) - Ivashutenko A. S. Alexander Sergeevich (Technologies of Electrophysical Methods of Materials Treatment, 2014)
Title screen